Embeddedness and the market's edge: Lakota artists at an economic fringe - Dorion, Patrick, author; Sherman, Kathleen, advisor; Galvin, Kathleen, committee member; Hammerdorfer, Carl, committee member (Colorado State University. Libraries, 2013)
The purpose of this research project is to investigate the liminal space Lakota people occupy between market and traditional economies. Rapid integration into a market-based economy and historical resistance to it has pushed the Lakota to an economic fringe, where cash needs demand that Lakota families engage with a market that does not sufficiently provide for them. On the Pine Ridge Reservation, Lakota people are able to absorb the limitations imposed by the market by engaging in a traditional economy embedded in social relations. In particular, this paper focuses on Lakota artists at this economic fringe, and discusses the decisions they make in order to survive.
Keywords: economic anthropology; Polanyi; Pine Ridge; Lakota; embeddedness